2022
DOI: 10.1038/s41419-022-04936-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive role of microRNA-139-5p in bone marrow mesenchymal stem cells-derived extracellular vesicles in bladder cancer through regulation of the KIF3A/p21 axis

Abstract: The emerging roles of extracellular vesicles (EVs) in bladder cancer have recently been identified. This study aims to elucidate the role of microRNA-139-5p (miR-139-5p) shuttled by bone marrow mesenchymal stem cells (BMSCs)-derived EVs (BMSCs-EVs) in bladder cancer, with the possible mechanism explored. Expression of miR-139-5p and KIF3A was tested, followed by an analysis of their correlation. EVs were isolated from BMSCs and co-cultured with T24 or BOY-12E cells with miR-139-5p mimic/inhibitor, oe-KIF3A, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Extracellular vesicles play critical roles in the communications between cells. Highly expressed miR-139-5p, which is poorly present in bladder cancer, is confirmed in bone marrow mesenchymal stem cell-derived extracellular vesicles . Therefore, specific, sensitive, and convenient quantification of clinically relevant miRNAs is highly needed. Moreover, since genes are always regulated by more than one miRNA, the multiplexing capability of a detection method is critical for practical utility.…”
mentioning
confidence: 99%
“…Extracellular vesicles play critical roles in the communications between cells. Highly expressed miR-139-5p, which is poorly present in bladder cancer, is confirmed in bone marrow mesenchymal stem cell-derived extracellular vesicles . Therefore, specific, sensitive, and convenient quantification of clinically relevant miRNAs is highly needed. Moreover, since genes are always regulated by more than one miRNA, the multiplexing capability of a detection method is critical for practical utility.…”
mentioning
confidence: 99%
“…The results have shown that the high expression of miR-20b-5p in tumor cells makes these cells more sensitive to radiation therapy, which has led to an increase in the efficiency of this treatment method [42]. Xiang et al showed that miR-139-5p in bone marrow mesenchymal stem cells (BMSCs) delays tumorigenesis and metastasis of bladder cancer cells in vivo by inactivating the p21 factor [43]. Also, microRNAs have an important regulatory role in diseases and are used as promising biomarkers for cancer diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the role of exosomes in cancer as well as the specific contributions in muscle invasive bladder cancer [ 82 , 85 , 86 ]. Additionally, to the above findings, there are several exosome biomarkers implicated in bladder cancer tumorigenesis [ 85 , 87 , 88 , 89 ]. These urine-based markers are characterized in Table 1 .…”
Section: Exosomes In Muscle Invasive Bladder Cancermentioning
confidence: 97%